PERSEPSI MASYARAKAT TERHADAP KEBERADAAN HUTAN TANAMAN INDUSTRI (HTI) PT. FINNANTARA INTIGA DI DESA TERATI KECAMATAN JANGKANG KABUPATEN SANGGAU - Deli, Deli; Oramahi, H A; Idham, M (JURNAL HUTAN LESTARI, 2019)
Terati Village is one of the villages in Jangkang District which has quite extensive forest resources. With the existence of HTI PT. Finnantara Intiga in Terati Village, it certainly can affect the socio-economic life of the communit. Industrial timber plantations (HTI) are production forest areas that apply intensive forestry cultivation (silviculture) to meet the raw material of the forestry industry, both timber and non timber. In the midst of the scarcity of natural production forests, HTI is the foundation of future forest product production. Exploitation of natural forest products since the 70s has become a significant source of state income. The method used is a survey method with interview techniques. Sampling was done intentionally (purposive sampling). The number of samples taken was 83 respondents who live in Terati Village. Characteristics of respondents taken are a minimum age of 19-65 years, Have lived at least 5 (five) years in the Village of Terati, Can read and write Healthy physically and spiritually. Data analysis consists of community perceptions, the relationship between age, knowledge, cosmopolitan and income and community perceptions.based on the results of data and calculations of the four variables for the age category with community income there is no relationship with community perception, while for the category of knowledge and cosmopolitan there is a real relationship with community perception. The observation shows that 17 respondents (20.48%) tend to have a high perception of the existence of HTI PT. Finnantara Intiga in Terati Village, Jangkang Subdistrict, Sanggau Regency, 52 respondents (62.65%) tended to have a moderate perception of the existence of PT. Finnantara Intiga in Terati Village, Jangkang District, Sanggau Regency and 14 (16.47%) respondents tended to have a low perception of the existence of PT. Finnantara Intiga in Terati Village, Jangkang District, Sanggau Regency. keywords: community perception, cosmopolitan,income with community perception,Â  influencing factors and knowledge.